TOWARDS A COMMON AGREEMENT ON EDUCATIONAL COOPERATION ON HUMAN RIGHTS EDUCATION IN ASEAN TO PROMOTE HUMAN RIGHTS AWARENESS FOR THE YOUTH - Satyawati, Ni Gusti Ayu Dyah (UI Scholars Hub, 2012)
The development of human resources through closer cooperation in education and life-long learning is one of ASEAN purposes as stipulated in the Article 1 Paragraph (10) of the ASEAN Charter. In the Cha-am Hua Hin Declaration on Strengthening Cooperation on Education to Achieve an ASEAN Caring and Sharing Community, the Heads of State and Government of ASEAN agreed to give greater emphasis on the principles of democracy, respect for human rights and peace-oriented values in the school curriculum. Indeed, that is an important action to strengthen the role of education in building the ASEAN Community by 2015. One of the ASEAN’s inspirations which are represented in ASEAN’s 5-year Work Plan on Education (2010-2015) is to prepare the youth for regional leadership. Based on that background, the awareness on human rights through human rights education for the youth as ASEAN future leader is very important. This paper will discuss two main issues, which are (1) how the educational cooperation in ASEAN can promote the human rights awareness for the youth? ; and (2) how the common agreement on human rights education to guide awareness for the youth can be achieved by ASEAN member states? Related with those issues, this paper will also analyze the right to education as enshrined in ASEAN member states’ constitution and analyze the CRC and other human rights instruments. The main recommendation: the steps to achieve the common agreement on human rights education by ASEAN member states that will strengthen the ASEAN’s role in sustainable development to promote human rights in the region.